1991
DOI: 10.1007/bf02171687
|View full text |Cite
|
Sign up to set email alerts
|

The effect of photosensitive dye Platonin on juvenile rheumatoid arthritis

Abstract: Two children with juvenile rheumatoid arthritis (JRA) were given photosensitive dye Platonin in combination with prednisolone. Analysis of clinical and laboratory data showed that Platonin was efficacious in the improvement of the clinical symptoms and the severity of inflammation, or in the maintenance of the remission state. There were no adverse side effects during long-term administration of medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…Furthermore, it is well known that PDGF transmits its signal into the intracellular space through the activation of AKT and mitogen-activated protein kinases (MAPKs) [8] . Platonin (4,4',4"-thrimethyl-3,3',3"-triheptyl-7-[2"-thiazolyl]-2,2'-trimethinethiazolocyanine-3-3"-diiodide) (Figure 1), a cyanine photosensitizing dye, is an immunomo dulator [9,10] currently in use as an effective medicine for rheumatoid arthritis [10,11] . Administration of platonin is known to inhibit the up-regulation of inflammatory molecules, including interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, and inducible nitric oxide synthase (iNOS) in endotoxin-activated macrophages [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is well known that PDGF transmits its signal into the intracellular space through the activation of AKT and mitogen-activated protein kinases (MAPKs) [8] . Platonin (4,4',4"-thrimethyl-3,3',3"-triheptyl-7-[2"-thiazolyl]-2,2'-trimethinethiazolocyanine-3-3"-diiodide) (Figure 1), a cyanine photosensitizing dye, is an immunomo dulator [9,10] currently in use as an effective medicine for rheumatoid arthritis [10,11] . Administration of platonin is known to inhibit the up-regulation of inflammatory molecules, including interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, and inducible nitric oxide synthase (iNOS) in endotoxin-activated macrophages [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Platonin, a cyanine photosensitizing dye, is a potent macrophage-activating agent (3,4) and an immunomodulator (5,6). It has been prescribed for rheumatoid arthritis (5,6).…”
mentioning
confidence: 99%
“…It has been prescribed for rheumatoid arthritis (5,6). Recently, we have provided evidence to demonstrate that platonin has beneficial effects on ameliorating endotoxemia in rat models (7).…”
mentioning
confidence: 99%
“…[10][11][12][13] It was reported that platonin, a kind of cyanine dye, suppressed acute endotoxemia in rats by inhibiting inflammatory cytokine release from lipopolysaccharide (LPS)-stimulated lymphocytes.…”
mentioning
confidence: 99%
“…[6][7][8][9] Some of those dyes have been used as immunomodulators to treat allergy and rheumatoid arthritis, and to promote wound-healing. [10][11][12][13] It was reported that platonin, a kind of cyanine dye, suppressed acute endotoxemia in rats by inhibiting inflammatory cytokine release from lipopolysaccharide (LPS)-stimulated lymphocytes. 14,15) Recent studies suggested that neutrophil infiltration and release of inflammatory cytokines (i.e., interleukin (IL)-1b, IL-6, IL-17, IL-23, and tumor necrosis factor-a) participate in a secondary mechanism of brain injury following ischemia and reperfusion.…”
mentioning
confidence: 99%